2014
DOI: 10.1039/c4nr05246c
|View full text |Cite
|
Sign up to set email alerts
|

A new phase transformation path from nanodiamond to new-diamond via an intermediate carbon onion

Abstract: The investigation of carbon allotropes such as graphite, diamond, fullerenes, nanotubes and carbon onions and mechanisms that underlie their mutual phase transformation is a long-standing problem of great fundamental importance. New diamond (n-diamond) is a novel metastable phase of carbon with a face-centered cubic structure; it is called "new diamond" because many reflections in its electron diffraction pattern are similar to those of diamond. However, producing n-diamond from raw carbon materials has so far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 35 publications
4
43
0
Order By: Relevance
“…In this study, the CQDs were synthesized by the LAL process, as reported by our group, [19][20][21][22] and then characterized. Figure 1A is an AFM image showing the morphology of CQDs.…”
Section: Results and Discussion Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the CQDs were synthesized by the LAL process, as reported by our group, [19][20][21][22] and then characterized. Figure 1A is an AFM image showing the morphology of CQDs.…”
Section: Results and Discussion Characterizationmentioning
confidence: 99%
“…The synthesis of CQDs using the LAL protocol was performed as previously described, [19][20][21][22] the process is in the Supplementary Materials section of the supplementary information.…”
Section: Synthesis Of Cqdsmentioning
confidence: 99%
See 2 more Smart Citations
“…carbon nanotubes, C 60 , glassy carbon, onion-like boron nitride and graphite) at extreme high pressure and high temperatures (HPHT). [21][22][23][24][25] A breakthrough was achieved by Tian's group in the fabrication of nt-diamond which is about two-fold harder than natural diamond, together with higher fracture toughness (15 MPa m 0.5 ) and in-air oxidation temperature. 3 Extensive experimental and theoretical studies had been devoted to further strengthening polycrystalline superhard materials, involving controlled creation of composted phases, internal defects, stacking faults and interface boundaries.…”
Section: Introductionmentioning
confidence: 99%